Obtaining a light-like planar gauge - Suzuki, A. T.; Bentin, R. (World Scientific Publ Co Pte Ltd, 2002)
In the usual and current understanding of planar gauge choices for Abelian and non-Abelian gauge fields, the external defining vector n(mu), can either be space-like (n(2) < 0) or time-like (n(2) > 0) but not light-like (n(2) = 0). In this work we propose a light-like planar gauge that consists of defining a modified gauge-fixing term, L-GF, whose main characteristic is a two-degree violation of Lorentz covariance arising from the fact that four-dimensional space-time spanned entirely by null vectors as basis necessitates two light-like vectors, namely n(mu) and its dual m(mu), with n(2) = m(2) = 0, n . m not equal 0, say, e.g. normalized to n . m = 2.
Keywords: noncovariant gauges; axial gauges; planar gauge